Design of a ceiling‐mounted reader antenna to maximize the readable volume coverage ratio for an indoor UHF RFID application. Issue 9 (September 2017) - Choo, J.; Yoo, S.; Choo, H.
Abstract: We propose a novel ceiling‐mounted reader antenna to achieve a specific readable volume for an indoor radio frequency identification (RFID) application. To satisfy various performances required for the indoor RFID application, a multilayered helix is adopted and optimized by a Pareto genetic algorithm in conjunction with a full‐wave electromagnetic field simulator. The optimized antenna is fabricated, and the measured results show a matching bandwidth of 15.4%, a CP bandwidth of 6.5%, and a maximum gain of 4.3 dBic. When the fabricated antenna is installed on the ceiling, the measured readable volume for both horizontally and vertically placed tags at 912 MHz is over 4.7 m 3 out of the target volume of 9 m 3 . Results verify that the proposed antenna is suitable for a reader antenna installed on ceiling in an indoor RFID application.